State-Aware Power and Rate Control Algorithm for EnergyHarvesting Wireless AD-H - Anjana Murali (Journal of Power Electronics and Devices, 2019)
The rate of transmission improvisation through optimum power usage is the main objective. An optimum power allocation method is defining here. Data transmission means computermediated communication among the users. Energy harvesting means generating source for transmission trough natural resources. By using Power allocation algorithm, throughput can be increased. Reinforcement learning is adopted here to make the system possible practically based on availability of causal knowledge. Power, bit-rate and buffer is generally modified in this system design. Practical conditions are created and studied in this research for the development of this multihop network. Minimum power consumption with the best rate of transmission is the basic need of this multihop communication system through the algorithm based operations.